Synthesis of Crosslinkable Alkali-Soluble Resins and Self-Crosslinking Polyacrylic Latexes - Min Li; Yansen Wang; Jun Ye; Longhai Guo; Haiqiao Wang (Molecules)
In the field of water-based inks, the use of alkali-soluble resins (ASRs) as polymeric surfactants for synthesizing polyacrylate latexes has become a mainstream method. This study first designed and prepared crosslinkable ASRs with a diacetone acrylamide (DAAM) crosslinking monomer via emulsion polymerization. These ASRs were then employed as surfactants to synthesize self-crosslinking polyacrylate latexes through an in situ one-pot method, systematically investigating the influence of crosslinkable ASRs on the properties of the corresponding polyacrylate latexes. The research revealed that all prepared polyacrylate latexes exhibited a core–shell structure. With increasing DAAM content in the ASRs, the latex particle size gradually increased while the particle size distribution narrowed. All latexes demonstrated excellent stability, with absolute ζ-potential values exceeding 30 mV. The introduction of DAAM into ASRs significantly increased the glass transition temperature in the high-temperature region of the corresponding latex films, with the tensile strength reaching a maximum of 7.96 MPa. Moderate crosslinking in ASRs substantially improved the water resistance of latex films. Crosslinking degree tests indicated that latex films prepared through either single shell-layer crosslinking or single core-layer crosslinking showed relatively low crosslinking degrees, while only the dual core–shell crosslinking strategy could effectively enhance the film crosslinking degree. However, excessively crosslinked shell layers significantly hindered the crosslinking reaction of DAAM in the core layer, leading to reduced overall film crosslinking. Additionally, incorporating a certain number of DAAM crosslinking groups in ASRs was found to improve the adhesion of corresponding water-based inks on PE and BOPP substrates, with adhesion on BOPP substrates reaching up to 100%.